Distributed ledger technology and digital assets policy and regulatory challenges in Asia. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It examines the evolution and typology of the emergent technology, its existing and projected applications, and regulatory and policy issues that they entail. This report highlights the trends, concerns, and potential opportunities of DLTs, especially for Asian markets. It also identifies the benefits and risks to using DLT and offers a functional and proportional approach to these issues.
Keywords: Blockchains (Databases) -- Law and legislation -- Asia; Data encryption (Computer science) -- Law and legislation -- Asia; Electronic funds transfers -- Law and legislation -- Asia; Information technology -- Asia; Electronic book